Tinjauan Kompilasi Hukum Islam terhadap Permohonan Dispensasi Nikah di Bawah Umur - Umi Habibah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Underage marriage dispensation is an application for waivers granted by the Religious Courts to prospective brides who are not old enough to marry, for men who have not reached the age of 19 years and women who have not reached the age of 16 years, based on Law No. 16 of 2019 concerning marriage. This study aims to find out the KHI review of the judge's considerations in determining the dispensation for underage marriage, and to find out what factors are considered by the judge at the Cibinong Religious Court in granting a dispensation application for underage marriage. The method used in this research is qualitative. Data collection techniques were carried out using interviews, observation or documentation. The results of the study show that based on the KHI review with its research findings, namely where KHI is the legal basis for bridging the marriage dispensation so that the marriage dispensation decision is implemented in overriding Law Number 16 of 2019 concerning marriage, as stated in Article 7 paragraph (2) and paragraph (4) regarding the age limit, namely the age of male and female candidates is at least 19 years old, where KHI is a review of judges' considerations in deciding to implement a marriage dispensation and the factors that are considered by judges in granting marriage dispensations at the Cibinong Religious Court, there are 4 factors including cultural factors, environmental factors, economic and educational factors, and the last factor is pregnancy out of wedlock. Keywords: KHI, Dispensation for Underage Marriage